Letter to the Editor 33(1) - Miah, Md Titu; Das, Aparna; Islam, Mohammad Rafiqul; Bala, Chandra Shekhar; Minnat, Baharul (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Abstract not available J Bangladesh Coll Phys Surg 2015; 33(1): 58-61